Ultrafine Magnetite Nanopowder: Synthesis, Characterization, and Preliminary Use as Filler of Polymethylmethacrylate Nanocomposites - Pietro Russo; Domenico Acierno; Mariano Palomba; Gianfranco Carotenuto; Roberto Rosa; Antonino Rizzuti; Cristina Leonelli (Journal of Nanotechnology)
Magnetite (Fe3O4) nanoparticles prepared by microwave-assisted hydrothermal synthesis have been characterized in terms of morphological and structural features. Electron micrographs collected in both scanning (SEM) and transmission (TEM) modes and evaluations of X-ray powder diffraction (XRD) patterns have indicated the achievement of a monodispersed crystallite structure with particles having an average size around 15–20 nm. Structural investigations by Micro-Raman spectroscopy highlighted the obtainment of magnetite nanocrystals with a partial surface oxidation to maghemite (γ-Fe3O4). Preliminary attention has been also paid to the use of these magnetite nanoparticles as filler for a commercial polymethylmethacrylate resin. Hybrid formulations containing up to 3 wt% of nanoparticles were prepared by melt blending and characterized by calorimetric and thermogravimetric tests. For sake of comparison, same formulations containing commercial Fe3O4 nanoparticles are also reported. Calorimetric characterization indicates an increase of both glass transition temperature and thermal stability of the nanocomposite systems when loaded with the synthesized magnetite nanoparticles rather then loaded with the same amount of commercial Fe3O4. This first observation represents just one aspect of the promising potentiality offered by the novel magnetic nanoparticles when mixed with PMMA.